The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/aen.12351
|View full text |Cite
|
Sign up to set email alerts
|

Description, natural history and genetic variation ofCaloptilia guacanivorasp. nov. Vargas‐Ortiz & Vargas (Lepidoptera: Gracillariidae) in the Atacama Desert, Chile

Abstract: Although considered the driest desert in the world, the Atacama provides unique habitats and a reservoir of biodiversity for plants and insects. Caloptilia Hübner, 1825 (Gracillariinae), is a highly diverse genus of leaf miner micromoths that has not yet been recorded in Chile. In this study, we describe a new species of Caloptilia from a relict, vulnerable ecotone in the transverse valleys of the Atacama Desert in northern Chile. Adults, immature stages and natural history, including the mine of Caloptilia gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…This could be attributed to the particular landscape configuration of the study area, which has relatively small patches of host plants separated by extensive hyperarid lands that appear to represent geographic barriers with low permeability to gene flow of these micromoths between patches. In relation to the geographic distribution of A. tecomae , the results provide molecular evidence in support of the only previous Peruvian record of this species, suggesting a relatively narrow geographic range restricted to a few ravines near the limit between Peru and Chile, as only the samples from Tacna-Arica showed divergence levels within the ranges previously reported as intraspecific for Gracillariidae [ 56 , 57 , 58 ]. This geographic range may be slightly wider, because T. f. fulva occurs in a few additional ravines in the southernmost part of Peru [ 18 ]; this micromoth should be searched for in all of them.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This could be attributed to the particular landscape configuration of the study area, which has relatively small patches of host plants separated by extensive hyperarid lands that appear to represent geographic barriers with low permeability to gene flow of these micromoths between patches. In relation to the geographic distribution of A. tecomae , the results provide molecular evidence in support of the only previous Peruvian record of this species, suggesting a relatively narrow geographic range restricted to a few ravines near the limit between Peru and Chile, as only the samples from Tacna-Arica showed divergence levels within the ranges previously reported as intraspecific for Gracillariidae [ 56 , 57 , 58 ]. This geographic range may be slightly wider, because T. f. fulva occurs in a few additional ravines in the southernmost part of Peru [ 18 ]; this micromoth should be searched for in all of them.…”
Section: Discussionsupporting
confidence: 86%
“…The divergence between haplotypes of Angelabella from different spatial genetic clusters (3.6–8.3% K2P) is either remarkably higher than [ 5 ] or near [ 6 , 12 ] those recorded between morphologically cryptic species of two other genera of Gracillariidae. Similar levels of divergence have been interpreted to represent putative heterospecific lineages in the absence of morphological evidence [ 12 , 17 , 58 ]. Despite the absence of obvious morphological differentiation between samples of Angelabella , the deep divergence between haplotypes of different spatial clusters, their reciprocal monophyly indicated by the phylogenetic analysis and the highly consistent results of the four species delimitation analyses suggest heterospecific status for the geographically isolated lineages analyzed.…”
Section: Discussionmentioning
confidence: 69%
“…Despite the extreme aridity of the Atacama Desert, some reports in the last decades suggest that it harbors a distinctive micro-moth fauna associated with native plants (e.g. Clarke 1987;Pereira et al 2017;Vargas-Ortiz et al 2019), which is reinforced by this study in which the taxonomic status of the Ithome pest of P. tamarugo in the Pampa del Tamarugal was assessed using morphology and DNA barcodes. The two character sources revealed that this micro-moth represents a previously undescribed species, here named I. tamarugensis.…”
Section: Discussionmentioning
confidence: 56%
“…Brito et al (2016) estimated that the diversity of the Neotropical Gracillariidae could be about 20 times greater than currently known, a suggestion that has been partially corroborated by recent additions, mainly based on findings undertaken in surveys for mines on native plants in little-studied Neotropical environments (e.g. Pereira et al 2017;Fochezato et al 2018;Moreira et al 2018;Vargas-Ortiz et al 2019).…”
Section: Introductionmentioning
confidence: 94%